Phytoplankton response to N-rich well amelioration brines: A mesocosm study from the southeastern Mediterranean Sea. (September 2019) - Raveh, Ofrat; Angel, Dror L.; Astrahan, Peleg; Belkin, Natalia; Bar-Zeev, Edo; Rahav, Eyal
Abstract: Human-induced eutrophication of coastal water may be a major threat to aquatic life. Here, we investigated the effects of N-rich well amelioration brines (WAB) on coastal phytoplankton population's habitat in the surface oligotrophic waters of the southeastern Mediterranean Sea (SEM). To this end, we added WAB (2 concentrations) to mesocosms (1-m 3 bags) to surface SEM water during summer and winter, where changes in phytoplankton biomass, activity and diversity was monitored daily for 8 days. Our results demonstrate that WAB addition triggered a phytoplankton bloom, resulting in elevated algal biomass (maximal +780%), increased primary production rates (maximal +675%) and a decrease in eukaryotic algal α-diversity ( ca . −20%). Among the species that bloomed following WAB amendments, we found the potentially toxic dinoflagellate Karlodinium venificum . This study adds valuable perspective to the effect of nutrients discharged into nutrient limited SEM coastal waters, and in particular of N-derived WAB. Graphical abstract: Unlabelled Image Highlights: The effects of well amelioration brines (WAB) on coastal phytoplankton were studied. WAB addition triggered an increase in algal biomass and primary production. The toxic dinoflagellate Karlodinium venificum bloomed following WAB amendments. WAB addition caused a decreased in phytoplankton α-diversity.